Topographical projection from the superior colliculus to the nucleus of the brachium of the inferior colliculus in the ferret: convergence of visual and auditory information. - Doubell, T; Baron, J; Skaliora, I; King, A (2000)
The normal maturation of the auditory space map in the deeper layers of the ferret superior colliculus (SC) depends on signals provided by the superficial visual layers, but it is unknown where or how these signals influence the developing auditory responses. Here we report that tracer injections in the superficial layers label axons with en passant and terminal boutons, both in the deeper layers of the SC and in their primary source of auditory input, the nucleus of the brachium of the inferior colliculus (nBIC). Electron microscopy confirmed that biocytin-labelled SC axons form axodendritic synapses on nBIC neurons. Injections of biotinylated dextran amine in the nBIC resulted in anterograde labelling in the deeper layers of the SC, as well as retrogradely labelled superficial and deep SC neurons, whose distribution varied systematically with the rostrocaudal placement of the injection sites in the nBIC. Topographical order in the projection from the SC to the ipsilateral nBIC was confirmed using fluorescent microspheres. We demonstrated the existence of functional SC-nBIC connections by making whole-cell current-clamp recordings from young ferret slices. Both monosynaptic and polysynaptic EPSPs were generated by electrical stimulation of either the superficial or deep SC layers. In addition to unimodal auditory units, both visual and bimodal visual-auditory units were recorded in the nBIC in vivo and their incidence was higher in juvenile ferrets than in adults. The SC-nBIC circuit provides a potential means by which visual and other sensory or premotor signals may be delivered to the nBIC to calibrate the representation of auditory space.